2013
DOI: 10.1093/cid/cit395
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cefepime for Treating AmpC β-Lactamase–Producing Enterobacteriaceae

Abstract: Cefepime may be a reasonable option for the treatment of invasive infections due to AmpC β-lactamase-producing organisms, particularly when adequate source control is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 39 publications
(61 reference statements)
1
79
0
3
Order By: Relevance
“…Using the current CLSI ceftriaxone breakpoint of 1 g/ml, we previously found that 100% of 96 organisms expressing AmpC ␤-lactamases had ceftriaxone MICs of Ͼ1 g/ml (11). Ceftriaxone has been found to be problematic for the treatment of these organisms, but broader-spectrum ␤-lactams have not demonstrated such problems (5).…”
mentioning
confidence: 99%
“…Using the current CLSI ceftriaxone breakpoint of 1 g/ml, we previously found that 100% of 96 organisms expressing AmpC ␤-lactamases had ceftriaxone MICs of Ͼ1 g/ml (11). Ceftriaxone has been found to be problematic for the treatment of these organisms, but broader-spectrum ␤-lactams have not demonstrated such problems (5).…”
mentioning
confidence: 99%
“…Besides, the resistance nature of amikacin was changed to susceptible, hence, it could be used as an alternate treatment approach in complementary and alternate medicine against S. marcescens infections in near future. However, cefepime is the preferred drug and useful in patients with nosocomial infections caused by aerobic Gram-negative bacilli, even effective against microbes, which are resistant to most of the third-generation cephalosporins and gentamicin [26,27]. Biofield treated S. marcescens results in improved antimicrobial sensitivity of cefepime and gentamicin from resistant to susceptible, while decreased the MIC value as compared to the control.…”
Section: Antimicrobial Susceptibility Testmentioning
confidence: 99%
“…Baseline data were collected for the first day of detectable bacteremia, Patients who (1) received corticosteroid therapy $2 mg/kg or $20 mg daily for at least 14 days, (2) received biologic agents in the preceding 30 days, (3) received a solid organ transplant, (4) received a hematopoietic stem cell transplant in the preceding 1 year, (5) received cancer chemotherapy within 6 months, (6) had a congenital immunodeficiency, or (7) had HIV with CD4 #200 cells/mL were categorized as immunocompromised. 21 Multidrug resistant Gram-negative (MDRGN) organisms were defined as organisms not susceptible (resistant or intermediate) to at least 1 agent in at least 3 of 6 antimicrobial drug classes, including aminoglycosides, anti-pseudomonal penicillins, third-generation cephalosporins, anti-pseudomonal fluoroquinolones, aztreonam, orcarbapenems. 22 Escherichia coli and Klebsiella spp were identified as extended spectrum b-lactamase (ESBL) producing when there was an increase in the zone of inhibition of $5 mm with either ceftazidime or cefotaxime discs when tested in combination with discs containing clavulanic acid.…”
Section: Data Collectionmentioning
confidence: 99%